La ville, quartier par quartier - Bérubé, Harold (Labour / Le Travail, 2016)
The article reviews and comments on the books, "Vivre en quartier populaire. Saint-Sauveur,1930–1980," by Dale Gilbert, and "Pointe-Saint-Charles. L’urbanisation d’un quartier ouvrier de Montréal, 1840–1930," by Gilles Lauzon.